3D Printing for Solid‐State Energy Storage. Issue 12 (5th November 2021) - Tian, Xiaocong; Xu, Bingang
Abstract: Ever‐growing demand to develop satisfactory electrochemical devices has driven cutting‐edge research in designing and manufacturing reliable solid‐state electrochemical energy storage devices (EESDs). 3D printing, a precise and programmable layer‐by‐layer manufacturing technology, has drawn substantial attention to build advanced solid‐state EESDs and unveil intrinsic charge storage mechanisms. It provides brand‐new opportunities as well as some challenges in the field of solid‐state energy storage. This review focuses on the topic of 3D printing for solid‐state energy storage, which bridges the gap between advanced manufacturing and future EESDs. It starts from a brief introduction followed by an emphasis on 3D printing principles, where basic features of 3D printing and key issues for solid‐state energy storage are both reviewed. Recent advances in 3D printed solid‐state EESDs including solid‐state batteries and solid‐state supercapacitors are then summarized. Conclusions and perspectives are also provided regarding the further development of 3D printed solid‐state EESDs. It can be expected that advanced 3D printing will significantly promote future evolution of solid‐state EESDs. Abstract : Advanced 3D printing of solid‐state energy storage devices including solid‐state batteries and solid‐state supercapacitors are comprehensively reviewed. Basic 3D printing features, critical manufacturing parameters, device optimization strategies, and in‐depth electrochemical studies are discussed to guide the future study and manufacturing of state‐of‐the‐art solid‐state energy storage devices.